Evaluation, characterization, and engine performance of complementary fuel blends of butanol–biodiesel–diesel from Aleurites moluccanus as potential alternative fuels for CI engines. Issue 5 (August 2020) - Atabani, AE; Mekaoussi, M; Uguz, Gediz; Arpa, Orhan; Ayanoglu, Abdulkadir; Shobana, Sutha
Biodiesel has gained worldwide attention due to its renewable aspects. However, it needs more quality improvement. Recently, butanol has been considered as a favorable alternative fuel or additive over methanol and ethanol in compression ignition (CI) engines. In this regard, the present work deals with the evaluation of butanol–diesel–biodiesel blends as potential alternative fuels. In this work, biodiesel has been produced from Aleurites moluccanus oil followed by blending with Euro-diesel and butanol. Important characteristics such as kinematic viscosity, density and cloud point besides FT-IR, UV-vis spectra, TGA, DSC and NMR ( 13 C and 1 H) were analyzed. Some important engine and emission performance parameters, such as BP, BSFC, CO, HC, NOx and EGT were also studied in this work. Results revealed that blending butanol and Euro-diesel with biodiesel improves the properties of pure biodiesel such as kinematic viscosity (2.41–3.55 mm 2 /s) and density (841.8–884.6 kg/m 3 ), while maintaining an acceptable range for cold flow properties that are analogous to Euro-diesel. In addition, reduction in BP (24.65–26.35%), HC (52.57–38.71%), and CO (39.18–30.4%) was observed for all the blends at full load compared to Euro-diesel. However, increases in both BSFC (38.17–41.14%) and NOx (24.18–8.35%) were observed. Overall, the blends appear to be good alternatives to biodiesel–diesel blends. Thus, butanol–biodiesel–diesel blends can be considered as potential sustainable fuels for fossil diesel.